2011
DOI: 10.3109/10428194.2011.553000
|View full text |Cite
|
Sign up to set email alerts
|

Pamidronate versus observation in asymptomatic myeloma: final results with long-term follow-up of a randomized study

Abstract: A prospective, multicenter, randomized trial comparing pamidronate administration (60-90 mg once a month for 1 year) versus simple observation in 177 patients with asymptomatic myeloma was performed to explore whether the administration of this drug reduces the rate of and/or the time to progression to overt, symptomatic disease. No relevant side effects were recorded in pamidronate-treated patients. With a minimum follow-up of 5 years for live patients, there were 56/89 (62.9%) progressions in the pamidronate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(45 citation statements)
references
References 25 publications
0
44
0
1
Order By: Relevance
“…The response rate was 37% in the thalidomide arm (whereas no responses were seen in the zoledronate arm), but there were no significant differences in the TTP to symptomatic MM (4.3 vs. 3.3 years) or in OS (74% vs. 73% at 5 years) [41]. Earlier trials of bisphosphonate treatment demonstrated the absence ofclearantitumoral effects, whereas a strong effect on the bone metabolism was uniformly described with a significant reduction in the incidence of skeletal-related events [42][43][44][45]. Given the anabolic effects on bone metabolism, bisphosphonates are recommended for those SMM patients with osteoporosis identified by dualenergy x-ray absorptiometry scan in doses used for osteoporosis [46].…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
“…The response rate was 37% in the thalidomide arm (whereas no responses were seen in the zoledronate arm), but there were no significant differences in the TTP to symptomatic MM (4.3 vs. 3.3 years) or in OS (74% vs. 73% at 5 years) [41]. Earlier trials of bisphosphonate treatment demonstrated the absence ofclearantitumoral effects, whereas a strong effect on the bone metabolism was uniformly described with a significant reduction in the incidence of skeletal-related events [42][43][44][45]. Given the anabolic effects on bone metabolism, bisphosphonates are recommended for those SMM patients with osteoporosis identified by dualenergy x-ray absorptiometry scan in doses used for osteoporosis [46].…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
“…Early intervention in the high-risk SMM group would avoid development of CRAB criteria and thus improve patients' survival. The current practice guidelines of withholding treatment until end-organ damage develops put patients at risk of renal failure 6 and adverse skeletal events. 7 This strategy of delaying treatment does not only influence patients' morbidity and overall costs, but also mortality, since renal insufficiency at diagnosis of MM has been shown to predict for inferior survival 8 except when bortezomib was included in the upfront management.…”
Section: Introductionmentioning
confidence: 99%
“…This supports the findings of several other studies in which the use of bisphosphonates always translated into a reduction of skeletal-related events. 8,9,[11][12][13][14][15][16]22 This reduction in skeletal-related events could also help to explain why the overall survival was marginally favored by the use of ZA, with a more pronounced effect in patients with bone disease or skeletal-related events, as the MRC trial had already demonstrated. 9 However, the number of patients and differences in this study are limited, which should be taken into consideration when interpreting the results.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%
“…Several studies have also evaluated the antitumor effect of bisphosphonate monotherapy in patients with asymptomatic/smoldering MM. [11][12][13][14][15][16] Although these studies demonstrated some benefit of bisphosphonates on bone resorption, no clear tumor responses or benefits in terms of progression-free or overall survival were observed. Patients with smoldering MM probably do not constitute the ideal target population for such studies because, given their low rate of progression, 24 a large number of patients and long follow up would be needed to demonstrate a survival benefit for a drug that would have only a minor antitumor activity, if any.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%
See 1 more Smart Citation